Use of Information Technologies in Higher Education From The Aspect of Management - Vesić, Dobrica; Laković, Duško; Vesić, Slavimir Lj. (International Journal of Cognitive Research in Science, Engineering and Education (IJCRSEE), 2023)
The development of modern information-communication technologies has enabled the development of electronic knowledge distribution channels that expand the effective level of general and specialist education. This trend is also present in higher education because higher education institutions and institutes increasingly rely on the use of modern information-communication technologies in their operations. The effects of the use of personal computers, the Internet and global social networks are multiple in the higher education system as well. In the process of acquiring new knowledge, developing creativity, as well as ensuring greater activity in the process of education, new learning technologies, with the use of multimedia systems, created the prerequisites for the engagement of all individual and collective resources. The most important source of the state’s competitive advantage is the ability to educate and retain highly educated personnel in the field of information technologies. From that aspect, the paper discusses information technologies as a scientific discipline and general conditions for education in the field of information technologies. The impact of technical and pedagogical changes on education in this area is analyzed with particular attention. It is known that information technologies are suitable for vocational education, and the modern environment sets specific requirements regarding the applicability of knowledge acquired in higher education institutions. The dynamic and turbulent market emphasizes the applicability of knowledge as a key requirement in the educational process. These short researches propose new educational modules that should structure teaching in the field of information technologies in accordance with the global demand in this sector. Every society strives for a more efficient and economical system of education, and therefore the issue of the use of new information technologies in education comes down to the problem of creating a theoretically ideal model of the use of these technologies at all levels of education and work.